(untitled) (Journal of Atomic and Molecular Sciences, 2014)
The general formalism of the Modified orbital atomic theory (MAOT) for the Rydberg series of atoms and ions is presented. Energy resonances of the 2s^22p^4(^1D_2)ns, nd, 2s^22p^4(^1S_0)ns, nd and 2s^2p^5(^3P_2)np Rydberg series originating from the 2s^22p^5 ^2P_1/2 metastable and from the 2s^22p^5 ^2P_3/2 ground state of Ne^+ are tabulate applying the MAOT formalism. Analysis of the present results is achieved in the framework of the standard quantum defect expansion formula. Comparison is done with the existing experimental and theoretical data.